Tungelsta med trädgårdstema - Dreierström, Cecilia (SLU/Dept. of Landscape Architecture, Planning and Management (from 130101), 2005)
In this project, an area in the small town Tungelsta south of Stockholm, is in focus. Tungelsta is placed in the municipality of Haninge and it is for the planning department on the municipality, this project is made.